1995
DOI: 10.1007/bf02032573
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin induced production of interleukin-6 is enhanced by vitamin E deficiency and reduced by black tea extract

Abstract: Studies were performed to investigate the effect of a polyphenol rich extract from black tea and vitamin E on bacterial lipopolysaccharide (endotoxin) induced IL-6 production, alterations in liver glutathione and antioxidant acute phase protein (caeruloplasmin) concentration, in rats fed on a synthetic diet for 21 days. In the vitamin E sufficient group a significantly lower IL-6 concentration than in vitamin E deficient animals was observed. Addition of tea extract to the diet produced a similar reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…In particular, IL-1β and IL-18, which belong to the IL-1 family of pro-inflammatory cytokines, are actively involved in an inflammatory response and the secretion of antibody under hyperthermia in animal models (Lin et al, 1994; Helwig and Leon, 2011). Similar to our observation, it has been reported that dietary supplementation of antioxidant vitamins decreased the expression of pro-inflammatory cytokines such as IL-6, IL-2 and TNF-α in rodents (Amarakoon et al, 1995; Yun et al, 2012). Yun et al (2012) also reported that in heat stressed rats dietary vitamin C supplementation produced significantly lower mRNA levels of hepatic IL-6 and TNF-α than controls.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, IL-1β and IL-18, which belong to the IL-1 family of pro-inflammatory cytokines, are actively involved in an inflammatory response and the secretion of antibody under hyperthermia in animal models (Lin et al, 1994; Helwig and Leon, 2011). Similar to our observation, it has been reported that dietary supplementation of antioxidant vitamins decreased the expression of pro-inflammatory cytokines such as IL-6, IL-2 and TNF-α in rodents (Amarakoon et al, 1995; Yun et al, 2012). Yun et al (2012) also reported that in heat stressed rats dietary vitamin C supplementation produced significantly lower mRNA levels of hepatic IL-6 and TNF-α than controls.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been reported that rats fed diets deficient in vitamin E after injections of endotoxin showed more anorexia and expressed higher IL-6 levels than animals consuming adequate amounts. 32) Lipid peroxidation was also found to be greater in the vitamin E-deficient animals in this study.…”
Section: Discussionsupporting
confidence: 61%
“…Original magnifications: )/80. was correlated with increased production of the proinflammatory cytokine IL-6, as compared with vitamin E-replete controls (16,25). Vitamin E is capable of inhibiting the activation of a transcription factor required for the expression of many pro-inflammatory cytokine genes, such as tumor necrosis factor-a (16,25).…”
Section: Discussionmentioning
confidence: 93%
“…There have been some experimental studies on suppression of inflammation by vitamin E. Rats made deficient in vitamin E showed exaggerated inflammatory reactions (16). Experimental peritonitis was suppressed by vitamin E supplementation in rats (17).…”
Section: Discussionmentioning
confidence: 98%